ANALISIS PENGARUH RASIO FINAL GEAR TERHADAP KECEPATAN DAN KONSUMSI BAHAN BAKAR MOBIL HYBRID URBAN KMHE 2018 - Poetro, Koerniawan Hastho (Universitas Mercu Buana, 2019)
In automotive world, differential ratio also known as final gear ratio. It consist of pinion gear and ring gear. Final gear ratio will be affecting car speed and fuel consumption that can be achieved. Research will be performed by experiment and data collection will be displayed through descriptive methode. Research began by selecting 2 kind of final gear ratio which are 1,27 and 2,53. Those ratios have been achieved by selecting pinion gear 15 and 30 teeth and ring gear 38 teeth, which are common and easy to find on the market. Testing performed by running the car on the tarmac testing track, 2800 meters (4 lap @700 meters), from stop until reached finish line with limited the speed test by 30 km/h and 40 km/h. Each test will be performed 5 times and the data collection will be displayed by tabulation and chart. The test results shown pinion gear with 30 teeth have less travelling time, less engine rotation and better fuel efficiency compare with pinion gear 15 teeth. Pinion gear 30 teeth have 8,9% better fuel consumption on 30 km/h speed and 4,7% better fuel consumption on 40 km/h.